2003
DOI: 10.1038/sj.onc.1206989
|View full text |Cite
|
Sign up to set email alerts
|

Second cancers after radiotherapy: any evidence for radiation-induced genomic instability?

Abstract: Do second primary cancers in humans arise from radiation-induced somatic genomic instability after radiotherapy for the first malignancy? The amount of truly pertinent human information on this issue is sparse, leading to the conclusion that we cannot confirm or refute that instability induction by radiation is involved. However, the in vitro findings of radiation-induced genomic instability through bystander effects or increased mutation rates in cell progeny of apparently normal but irradiated cells are prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Ionizing radiation is a known carcinogen that has been implicated in the etiology of a number of human tumors, including breast cancer, glioma, lymphoma and sarcoma , but the role of induced genetic instability in the process of human carcinogenesis remains controversial (Marx, 2002;Sigurdson and Jones, 2003). Radiation causes damage to DNA directly by the induction of double strand breaks (DSBs), or indirectly by generation of reactive oxygen species that damage sugar and base residues.…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation is a known carcinogen that has been implicated in the etiology of a number of human tumors, including breast cancer, glioma, lymphoma and sarcoma , but the role of induced genetic instability in the process of human carcinogenesis remains controversial (Marx, 2002;Sigurdson and Jones, 2003). Radiation causes damage to DNA directly by the induction of double strand breaks (DSBs), or indirectly by generation of reactive oxygen species that damage sugar and base residues.…”
Section: Introductionmentioning
confidence: 99%
“…10,23,24 It has been suggested that the radiation-induced bystander effects, including genomic instability and increased mutation, may contribute to second cancer induction in normal cells after radiotherapy. 25 Most of the previous studies of bystander effects focused on the radiation-induced responses within a cell population or cluster consisting of the same cell type. Recently, however, bystander responses have been reported in a 3-dimensional ureter primary tissue model after microbeam irradiation.…”
mentioning
confidence: 99%
“…The recognition that second cancers in patients who have received radiotherapy are related to the treatment for their first malignancy provided the focus for a recent review which examined whether such cancers could have arisen from radiation-induced genomic instability [39]. However, it was concluded that current studies do not provide sufficient evidence to determine if the phenomenon contributes to secondary malignancies after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%